Online Learning Readiness of Junior High School Students in Denpasar - Kadek Erlita Dwiyanti; I Putu Yogi Pratama; Ni Putu Ines Marylena Candra Manik (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2020)
ABSTRACTThe Covid-19 pandemic has caused learning to be carried out online. Not all students, however, are ready for online learning. This study aims to examine the level of readiness of eighth-grade students at a junior high school through an explanatory sequential mixed method design consisting of quantitative and qualitative phases. Student readiness for online learning in this study was reviewed from five dimensions: self-directed learning, motivation for learning, computer/internet self-efficacy, learner control, and online communication self-efficacy. The Online Learning Readiness Scale (OLRS) survey proposed by Hung (2010) with a five-point-Likert scale was used to collect quantitative data. The data were analyzed quantitatively, and the level of readiness was measured utilizing the e-learning readiness assessment model suggested by Aydin and Tasci (2005). Follow-up interviews were then held to support the quantitative data. The results showed that the majority of students entered the level of